Method for aggregating triangular fuzzy intuitionistic fuzzy information and its application to decision making - Zhang, Xin; Liu, Peide (Technological and Economic Development of Economy, 2010)
On the foundation of the theory of the intuitionistic fuzzy set, this paper uses the triangular fuzzy number to denote the membership degree and the non‐membership degree and proposes the triangular intuitionistic fuzzy number. Then the operation rules of triangular intuitionistic fuzzy numbers are defined. The weighted arithmetic averaging operator and the weighted geometric average operator are presented and used to the decision making area after defined the score function and the accuracy function. An effective solution is offered for multi‐attitude decision‐making problem and an active try is made.Article in English.Numanomų neapibrėžtųjų aibių teorija ir jos taikymas priimant sprendimusSantrauka. Remiantis numanomų neapibrežtųjų aibių teorija, šiame straipsnyje aprašomas trečiojo laipsnio neapibrežtasis skaičius, apibūdinantis priklausomumo laipsni. Toliau nustatomos operavimo su tokiais skaičiais taisyklės. Pasiūlytas svertinis aritmetinio vidurkio operatorius, naudojamas priimant sprendimus. Siūlomi efektyvūs daugiaaspekčių problemų sprendimo būdai.Reikšminiai žodžiai: numanomas neapibrežtasis skaičius, numanomas trečiojo laipsnio neapibrežtasis skaičius, integracijos operatorius, sprendimu priemimas.First published online: 09 Jun 2011